The long-run effects of peers on mental health - Lukas Kiessling; Jonathan Norris (Max Planck Institute for Research on Collective Goods, 2020)
This paper studies how peers in school affect students' mental health. Guided by a theoretical framework, we find that increasing students' relative ranks in their cohorts by one standard deviation improves their mental health by 6% of a standard deviation conditional on own ability. These effects are more pronounced for low-ability students, persistent for at least 14 years, and carry over to economic long-run outcomes. Moreover, we document a strong asymmetry: Students who receive negative rather than positive shocks react more strongly. Our findings therefore provide evidence on how the school environment can have long-lasting consequences for the well-being of individuals.
hdl:21.11116/0000-0006-7580-5
Keywords: I21; I14; J24; 330; Peer Effects; Mental Health; Depression; Rank Effects